Inhibition of gamma-secretase activity without interfering in Notch signalling decreases inflammatory response in patients with cutaneous leishmaniasis - Maurício T. Nascimento; Mônica Franca; Augusto M. Carvalho; Camila F. Amorim; Fábio Peixoto; Daniel Beiting; Phillip Scott; Edgar M. Carvalho; Lucas P. Carvalho (Emerging Microbes and Infections)
Cutaneous leishmaniasis (CL) patients present an exacerbated inflammatory response associated with tissue damage and ulcer development. Increasing numbers of patients have exhibited treatment failure, which remains not well understood. We hypothesized that adjuvant anti-inflammatory therapy would benefit CL patients. The aim of the present study was to investigate the contribution of Notch signalling and gamma-secretase activity to the inflammatory response observed in CL patients. Notch signalling is a molecular signalling pathway conserved among animal species. Gamma-secretase forms a complex of proteins that, among other pathways, modulates Notch signalling and immune response. We found that Notch 1 cell receptor signalling protects against the pathologic inflammatory response, and JLK6, a gamma-secretase inhibitor that does not interfere with Notch signalling, was shown to decrease the in-vitro inflammatory response in CL. Our data suggest that JLK6 may serve as an adjuvant treatment for CL patients.